Is the Complete Resection of Craniopharyngiomas in Adults Feasible Considering Both the Oncologic and Functional Outcomes? - Lee, Eun Jung; Cho, Young Hyun; Hong, Seok Ho; Kim, Jeong Hoon; Kim, Chang Jin (Journal of Korean Neurosurgical Society, 2015)
To assess the impact of the complete resection of craniopharyngioma (CP) in adults on oncologic and functional outcomes. We retrospectively analyzed 82 patients with CP who were surgically treated by the same neurosurgeon at our institution between January 1994 and December 2012. Gross total resection (GTR) was achieved in 71 patients (86.6%), near total resection (NTR) in 7 patients (8.5%), and subtotal resection (STR) in 3 patients (3.7%). The disease-specific overall survival rate was 100% with the exclusion of 2 surgery-related mortalities. The overall recurrence rate was 12.2% (10 of 82 patients), however the recurrence rate according to extent of resection (EOR) was 9.9% (7 of 71 patients) after GTR, 14.3% (1 of 7 patients) after NTR, and 66.7% (2 of 3 patients) after STR. The overall recurrence-free survival (RFS) rates at 5 and 10 years were 87.0% and 76.8%, respectively. Postoperatively, most patients (86.3%) needed hormone replacement for at least 1 hypothalamic-pituitary axis. Vision improved in 56.4% of the patients with preoperative abnormal vision, but deteriorated in 27.4% of patients. Hypothalamic dysfunction developed in 32.9% of patients. There were no significant differences in the risks of pituitary dysfunction, visual deterioration, or hypothalamic dysfunction between the groups with complete vs. incomplete removal. The overall rate of postoperative complications was 22.0%, which did not differ between groups (p=0.053). The complete removal of a CP at first surgery can provide a chance for a cure with acceptable morbidity and mortality risks.